Why is Reflexivity so Special? Understanding the World of Reflexives1. (April 2017) - Reuland, Eric
Abstract: Why do so many languages employ special means to express reflexive predicates, and why can what languages do be so diverse, although the notion of a reflexive predicate appears to be so simple? What happens in languages that don't seem to do anything special? The contributions in this special issue all focus on the various ways in which natural languages express reflexivity, and how the challenges their diversity poses can be addressed. In this contribution I present and further develop my answers to these questions, showing that except for a definition of binding no principles specific to binding need to be assumed. Sections 3–7 provide an overview of issues against which the results of current binding research are to be interpreted. I briefly address the role of phases in the theory of binding and argue that phases are relevant only indirectly namely in so far as the operations involved in the encoding of binding dependencies are themselves sensitive to phase‐hood. I also relate my account to current debates about the relation between syntax and morphology (as in Distributed Morphology), showing that a too loose connection between syntax and morphology leads to severe methodological problems. Section 8, presents an explicit derivation of the need for reflexivity to be licensed, addressing questions that have been raised since that idea was first presented. Section 9 provides a summary of the approach.